"Lucas" in the laboratory - Elena Asparouhova; Peter Bossaerts; Nilanjan Roy; William Zame (Institute for Advanced Studies (IHS), 2015)
The Lucas asset pricing model is studied here in a controlled setting. Participants could trade two long-lived securities in a continuous open-book system. The experimental design emulated the stationary, infinite-horizon setting of the model and incentivized participants to smooth consumption across periods. Consistent with the model, prices aligned with consumption betas, and they co-moved with aggregate dividends, more strongly so when risk premia were higher. Trading significantly increased consumption smoothing compared to autarky. Nevertheless, as in field markets, prices were excessively volatile. The noise corrupted traditional GMM tests. Choices displayed substantial heterogeneity: no subject was representative for pricing.
Keywords: 330